Vibration based damage detection in hyperbolic cooling towers using coupled method. (March 2021) - Randiligama, S.M. Chathurangi M.; Thambiratnam, David P.; Chan, Tommy H.T.; Fawzia, Sabrina; Duy Nguyen, Khac
Highlights: Coupled vibration-based method was developed to predict damage in cooling towers. This method requires only the first few global vibration modes. Effects of noise and limited number of data points are considered. Proposed method and modelling techniques are validated using test results. Outcomes enable timely retrofitting to prevent failure of these large structures. Abstract: Hyperbolic cooling towers are high rise reinforced concrete structures that are built to last a long time. Their primary task is to remove the heat from the wastewater and transfer it to the atmosphere using the process of evaporation. Hence these structures are subjected to large temperature variations. These along with material degradation, environmental effects, and random actions can initiate damage in these structures. Such damage can go undetected as a significant part of a hyperbolic cooling tower is neither easily visible nor accessible. Determining the onset of damage and carrying out appropriate retrofitting is important to prevent the failure or collapse of these large structures. Relatively few studies have been carried out on damage detection in cooling towers. This paper develops and applies a coupled method based on vibration characteristics using the absolute change in mode shape curvature to detect and locate damage in hyperbolic cooling towers. The coupled method considers few vertical cross-sections to first determine the height of the damage and then its position on the horizontal cross-section at that height of the axisymmetric cooling tower. The proposed damage detection method and modelling techniques are validated using data from experimental testing of laboratory-scale cooling tower models. Effects of noise and limited number of data points are considered to represent practical circumstances. Results confirm that the proposed method is very effective in detecting and locating damage in hyperbolic cooling towers under a range of damage scenarios using the first few global vibration modes. Findings of this paper will contribute towards enhanced safety of these large structures and help to prevent their failure.